Antitubulin effects of aminobenzothiophene-substituted triethylated chromones. Issue 12 (15th June 2017) - Kobayashi, Yukiko; Saito, Yohei; Goto, Masuo; Nakagawa-Goto, Kyoko
Graphical abstract: Abstract: In the course of our continuing studies on the 2-(benzo[ b ]thiophene-3′-yl)-6, 8, 8-triethyldesmosdumotin B (TEDB-TB) series, we designed and synthesized nine amino-TEDB-TB derivatives to improve pharmaceutical properties, identify structure activity relationships, and discover novel antitubulin agents. Among all newly synthesized amino-TEDB-TBs, the 5′- and 6′-amino derivatives, 6 and7, exhibited significant antiproliferative activity against five human tumor cell lines, including an MDR subline overexpressing P-gp. The IC50 values of 0.50–1.01 µM were 3–6 times better than those of previously reported hydroxy-TEDB-TBs. Compounds6 and7 inhibited tubulin polymerization, induced both depolymerization of interphase microtubules and multiple spindle formations, and caused cell arrest at prometaphase. Among all compounds, compound7 scored best pharmaceutically with LogP 2.11 and biologically with greater antiproliferative activity and induction of cell cycle arrest at prometaphase.